2023
DOI: 10.1037/fam0001109
|View full text |Cite
|
Sign up to set email alerts
|

Strengths-based spillover models: Constructive interparental conflict, parental supportive problem solving, and development of child executive functioning.

Abstract: Empirical research examining the Spillover Hypothesis has largely substantiated that interparental conflict comprised of hostility and anger has negative implications for parenting behaviors and cascading effects on children's development. However, less is known about how constructive forms of interparental conflict may operate in spillover processes. Toward this, the present study examined how interparental supportive and problem-solving approaches to conflict were associated with parental guided learning in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…A substantial number of studies have examined the impact of marital conflict on the negative function of adolescents while ignoring the role of marital intimacy ( Erath et al, 2006 ; Philbrook et al, 2018 ; Swerbenski et al, 2023 ). Based on family system theory, we extended previous studies by including both marital conflict and intimacy, as well as depressive symptoms and aggressive behavior, in an integrated model.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A substantial number of studies have examined the impact of marital conflict on the negative function of adolescents while ignoring the role of marital intimacy ( Erath et al, 2006 ; Philbrook et al, 2018 ; Swerbenski et al, 2023 ). Based on family system theory, we extended previous studies by including both marital conflict and intimacy, as well as depressive symptoms and aggressive behavior, in an integrated model.…”
Section: Discussionmentioning
confidence: 99%
“…An open and positive marital relationship can provide emotional support, a source of delight and purpose in life for adolescents, which are vital to their mental health and psychosocial adjustment ( Li et al, 2020 ; Zhang et al, 2022 ). In contrast, exposure to marital conflict may evoke adolescents’ fear, pain, vigilance and hostility, potentially leading to depression and other mental illnesses ( Cummings et al, 2012 ; Swerbenski et al, 2023 ). Thus, fostering a harmonious marital relationship may serve as a pivotal factor in mitigating adolescent depressive symptoms and aggressive behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to authoritarian discipline, which has received considerable attention in the IPC spillover literature (Harold & Sellers, 2018), there are no direct tests of the proposition that IPC affects parental scaffolding behavior, despite the influence of scaffolding on optimal child development (e.g., Jones-Gordils et al, 2021). Swerbenski et al (2023) found that constructive IPC was positively associated with parental scaffolding behavior. The omission of studies examining scaffolding behavior is partly a result of the IPC spillover literature focusing heavily on the discipline domain of parenting.…”
Section: Guided Learning Domainmentioning
confidence: 99%